Translating Preclinical Research for Exercise Oncology: Take It to the VO2max - Lamkin, Donald M.; Garland, Theodore (Frontiers in Oncology, 2020)
Several observational studies have found that the risk for breast cancer is significantly reduced in persons who engage in greater amounts of physical activity. Additional observational studies of breast cancer survivors indicate that greater physical activity before or after diagnosis associates with reduced disease-specific mortality. However, no large randomized controlled trials have examined the effect of structured exercise training on disease outcomes in breast cancer. Among the many hurdles in designing such trials lies the challenge of determining how a given regimen of exercise from efficacious preclinical studies can be extrapolated to an equivalent "dose" in humans to guide decisions around treatment regimen in early phase studies. We argue that preclinical researchers in exercise oncology could better facilitate this endeavor by routinely measuring changes in exercise capacity in the subjects of their breast cancer models. VO2max, the maximal rate of whole-organism oxygen consumption during a progressive exercise test, is emphasized here because it has become a standard measure of cardiorespiratory fitness, is well-integrated in clinical settings, and scales allometrically between non-human animals in preclinical research and breast cancer patients / survivors in the clinic. We also conduct secondary analyses of existing whole-transcriptome datasets to highlight how greater uptake and delivery of oxygen during exercise may reverse the typically hypoxic microenvironment of breast tumors, which often associates with more aggressive disease and worse prognosis.